Incorporating circulating cytokines into the idiopathic inflammatory myopathy subclassification toolkit - De Paepe, Boel (Frontiers in Medicine, 2023)
Extensive diagnostic delays and deferred treatment impact the quality of life of patients suffering from an idiopathic inflammatory myopathy. In-depth subtyping of patients is a necessary effort to engage appropriate disease management and may require specialized and elaborate evaluation of the complex spectrum of clinical and pathological disease features. Blood samples are routinely taken for diagnostic purposes, with creatine kinase measurement and autoantibody typing representing standard diagnostic tools in the clinical setting. However, for many patients the diagnostic odyssey includes the invasive and time-consuming procedure of taking a muscle biopsy. It is proposed that further implementation of blood-based disease biomarkers represents a convenient alternative approach with the potential to reduce the need for diagnostic muscle biopsies substantially. Quantification of judicious combinations of circulating cytokines could be added to the diagnostic flowchart, and growth differentiation factor 15 and C-X-C motif chemokine ligand 10 come forward as particularly good candidates. These biomarkers can offer complementary information for diagnosis indicative of disease severity, therapeutic response and prognosis.